A lanthanide ion-doped Ba3Sc2F12 phosphor: hydrothermal synthesis, morphological control, energy transfer, and temperature-sensing performance. Issue 18 (20th April 2020) - Mao, Yini; Jiang, Li; Hu, Shanshan; Tang, Jianfeng; Luo, Yu; Ding, Xiaoyu; Chen, Guannan; Yang, Jun
Abstract : Ba3 Sc2 F12 crystals were synthesized by a facile one-step hydrothermal method with Ba/Sc raw material in a ratio of 3 : 2. Abstract : Ba3 Sc2 F12 crystals were synthesized by a facile one-step hydrothermal method with Ba/Sc raw material in a ratio of 3 : 2. With the F/Sc ratio increasing from 4 to 8, the obtained crystal's morphology evolved gradually from a strip to a chocolate shape; further, the use of the additives, such as CTAB and EDTA, the obtained crystal's morphology changed from strip to cubic. The energy transfer of Ce 3+ → Tb 3+ in the Ba3 Sc2 F12 host was also explored, and it was found to belong to a dipole–dipole interaction mechanism; the color of the light could be adjusted from blue-violet to green due to the different energy transfer efficiencies at different Ce 3+ and Tb 3+ ion-doping concentrations. Because of the thermal coupling level of Er 3+ ( 2 H11/2 → 4 I15/2 and 4 S3/2 → 4 I15/2 ), Ba3 Sc2 F12 :14%Yb 3+, 2%Er 3+ phosphors showed an excellent temperature-sensing ability with S A(max) = 0.0043 K −1 and T max = 523 K, which are much better than the previously reported values for Yb 3+ /Er 3+ co-doped systems. The as-prepared lanthanide ion-doped phosphors might have potential to serve as color light/displays and temperature control/sensors.